Formation OF ZINC OXIDE THIN FILMS BY COMBINED METHOD OF HYDROTHERMAL AND LAYERED ATOM DEPOSITION - E. B. Chubenko; V. P. Bondarenko; V. A. Pilipenko; K. .. Topalli; A. K. Okyay (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Properties and deposition of continuous thin zinc oxide films by chemical on the monocrystalline silicon substrates with zinc oxide seed layer formed by atomic layer deposition are studied. Obtained hybrid zinc oxide structures consist of vertically oriented crystallites packed in uniform continuous film. Optical and electrical properties of the films are measured. It is shown, that deposited zinc oxide films demonstrate photoluminescence in the visible range of electromagnetic spectra with maximum at 600-700 nm. Luminescence band in the near UV region at 380 nm, associated with band-to-band radiative recombination, is also measured. The resistivity of the obtained zinc oxide films is about 0.7 Ohm·cm.